1997
DOI: 10.1046/j.1365-2168.1997.02771.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a biofragmentable bowel anastomosis ring in high-risk colonic resection

Abstract: This study shows that the BAR anastomosis probably is as safe as the standard band-sewn anastomosis in high-risk colorectal surgery. As the cost of a BAR anastomosis is substantially higher than that for a hand-sewn anastomosis, the latter technique is still the preferred method in the authors' unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…Recently published data from a European multicenter trial on compression anastomoses confirm these results: after 1,666 BAR anastomoses in the gastrointestinal tract a clinical leakage rate of 2.04% was reported [10]. Even high-risk colonic resections and anastomoses in previously irradiated colon reveal a low leakage rate of 4% [19]. …”
Section: Discussionsupporting
confidence: 63%
“…Recently published data from a European multicenter trial on compression anastomoses confirm these results: after 1,666 BAR anastomoses in the gastrointestinal tract a clinical leakage rate of 2.04% was reported [10]. Even high-risk colonic resections and anastomoses in previously irradiated colon reveal a low leakage rate of 4% [19]. …”
Section: Discussionsupporting
confidence: 63%
“…The development of compression anastomosis began with Denan in 1826 followed by the simpler metallic Murphy's button in 1892 [3,4,7,8]. The Russians made the AKA-2 device in 1984 and Hardy and colleagues developed the Valtrac ring in 1985 [3,4,7,8,9,10,11,12,13,14,15,16,17]. In 2006, a nickel-titanium shape memory ring device was described in the literature [5,18,19,20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body reactions characterized by pathological inflammation might cause disturbed anastomotic healing contributing to leakage and stricture formation [3,4]. Numerous studies using the Valtrac ring have documented that the concept of compression anastomosis is safe for intestinal anastomoses in the gastrointestinal tract [3,4,7,8,9,10,11,12,13,14,15,16,17]. In fact, randomized investigations have also shown that the Valtrac ring is safe for colorectal anastomoses in patients at risk [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…141 Today the biofragmentable anastomotic ring, made of absorbable polyglycolic acid, is used most often. Four included experimental studies [107][108][109][110] showed that compression colorectal anastomosis leads to acceptable healing and strength; 6 included RCTs [111][112][113][114][115][116] provide equivalent conclusions, finding no significant differences between hand-sewn and compression colorectal anastomosis. Also, noncomparative clinical cohort studies [142][143][144][145] including up to 1360 patients have reported incidences of AL between 0.7% and 5%.…”
Section: Hand-sewn Vs Compression Colorectal Anastomosismentioning
confidence: 99%